KOLABORASI DALAM PELATIHAN PENULISAN KARYA ILMIAH MAHASISWA MENGGUNAKAN MEDIA DARING - Febriyanti, Doris; Zubaidah, Siti; Yuslaini, Nina (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2024)
This training activity aims to optimize students' ability to write and publish scientific papers through coordinated online training. The training, which was held on Saturday, May 25, 2024, involved 150 students from various universities in Indonesia, including Indo Global Mandiri University, STIA Bala Putra Dewa, Universitas Terbuka, Sriwijaya University, UIN Walisongo University Semarang, Jakarta State University, Palembang Ministry of Health Polytechnic, and STIE Aprin Palembang. The method of the activity is planned by identifying problems, carried out online through WhatsApp Groups and Zoom Meetings, including three sessions of delivering interesting material about scientific publications and writing. Each session began with an opening by the MC, prayer reading, and singing the Indonesia Raya song, followed by material presentations by three speakers. This training is designed to overcome students' limited knowledge in scientific writing and utilize digital technologies, including Artificial Intelligence, to improve the quality and effectiveness of their scientific work. Through this program, it is hoped that students can better understand the process of scientific writing and publication, so that they can produce works that are of higher quality and ready to be published.